Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1051/matecconf/201819202040
|View full text |Cite
|
Sign up to set email alerts
|

Estimating sediment delivery ratio by stream slope and relief ratio

Abstract: Nowadays, the storage capacity of a reservoir reduced by sediment deposition is a concern of many countries in the world. Therefore, understanding the soil erosion and transportation process is a significant matter, which helps to manage and prevent sediments entering the reservoir. The main objective of this study is to examine the sediments reaching the outlet of a basin by empirical sediment delivery ratio (SDR) equations and the gross soil erosion. The Shihmen reservoir watershed is used as the study area.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The SDR is controlled by many factors, such as land use, catchment area, relieflength ratio, soil texture, transport process and gradient gradient of the main channel. Many studies have examined the relationship between SDR and the above factors (Kieu Anh Nguyen and Walter Chen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The SDR is controlled by many factors, such as land use, catchment area, relieflength ratio, soil texture, transport process and gradient gradient of the main channel. Many studies have examined the relationship between SDR and the above factors (Kieu Anh Nguyen and Walter Chen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Soil loss in the watershed of the Shihmen Reservoir, Taiwan, was over 9700 t/km 2 /year [5,6]. Nguyen and Chen [7] showed that the Shihmen is to predict long-term soil erosion and predict sediment yield in the reservoir, due to climate change, to improve the declining capacity of the reservoir and water planning and management. A Global Climate Model (GCM), Institute Pierre Simon Laplace-Climate Model version 5A (IPSL-CM5A-MR) from Coupled Model Intercomparison Project-5 (CMIP5) and three scenarios, i.e., RCP 2.6, RCP 4.5, and RCP 8.5, in the LPP watershed, were used to predict future rainfall data via Sananmuang's method [21], from the correlation between rainfall and water surface in the central part of Thailand [22,23].…”
Section: Introductionmentioning
confidence: 99%